2015
DOI: 10.1007/s10482-015-0388-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel killer protein from Pichia kluyveri isolated from an Algerian soil: purification and characterization of its in vitro activity against food and beverage spoilage yeasts

Abstract: A novel killer protein (Pkkp) secreted by a Pichia kluyveri strain isolated from an Algerian soil was active against food and beverage spoilage yeasts of the genera Dekkera, Kluyveromyces, Pichia, Saccharomyces, Torulaspora, Wickerhamomyces and Zygosaccharomyces. After purification by gel filtration chromatography Pkkp revealed an apparent molecular mass of 54 kDa with SDS-PAGE. Minimum inhibitory concentrations (MICs) of purified Pkkp exhibited a high in vitro activity against Dekkera bruxellensis (MICs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…Additionally, a novel killer protein produced by P . kluyveri has been shown to inhibit the growth of some food and beverage spoilage yeasts (Labbani et al ., ).…”
Section: Pichia Sppmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, a novel killer protein produced by P . kluyveri has been shown to inhibit the growth of some food and beverage spoilage yeasts (Labbani et al ., ).…”
Section: Pichia Sppmentioning
confidence: 97%
“…Additional biotechnological applications of P. kluyveri include: shaping chocolate flavour profile during cocoa fermentation (Crafack et al, 2013(Crafack et al, , 2014; potential for tequila fermentation (Amaya-Delgado et al, 2013); and a role as a probiotic (Tiago et al, 2009). Additionally, a novel killer protein produced by P. kluyveri has been shown to inhibit the growth of some food and beverage spoilage yeasts (Labbani et al, 2015).…”
Section: Pichia Sppmentioning
confidence: 99%
“…Potentially, P. kluyveri has a positive influence on the flavor of CHP. Further, Labbani et al (2015) found that a novel killer protein secreted by a P. kluyveri strain was active against yeasts. This possibly accounted for the decrease of the Geotrichum candidum in the fermentation process of CHP.…”
Section: Dynamics Of Microbial Community During the Whole Fermentationmentioning
confidence: 99%
“…Apart from the use of P. membranifaciens CYC 1086 and PMKT2, killer toxins from Ustilago maydis [10], Torulaspora delbrueckii (TdKT) [9], Kluyveromyces wickerhamii (Kwkt), Wickerhamomyces anomalus (Pikt) [183] and Candida pyralidae (CpKT1) [184] and the production of pulcherriminic acid by Metschnikowia pulcherrima (without a real killer activity but depleting biologically available iron from the medium) [190] have been reported as useful to control Brettanomyces spoilage. Continuing in the enology context, results from Alonso et al (2015) and Labbani et al (2015) conclude that a synergistic effect was operating using PMKT [185] and Pkkp (from P. kluyveri ) [8] killer toxins, respectively, in combination with potassium metabisulfite, against wine spoilage yeasts such as Zygosaccharomyces or Dekkera/Brettanomyces species. Recently, Velazquez and coworkers described the utility of mixed-inoculation with killer and sensitive yeast strains to speed cell death during second fermentation of sparkling-wines to release of certain compounds from autolyzed yeast cells [181].…”
Section: Applications Conclusion and Future Perspectives Of P Mmentioning
confidence: 99%
“…Over 11 different killer toxins have been described, and they are produced by representatives of such genera as Hanseniaspora , Pichia , Saccharomyces , Torulaspora , Ustilago , Williopsis , etc. (Table 1) [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%